2020
DOI: 10.3390/genes11101167
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Effect of Methylation of the Porcine AQP3 Gene Promoter Region on Its Expression Level and Porcine Epidemic Diarrhea Virus Resistance

Abstract: As an important carrier for intestinal secretion and water absorption, aquaporin 3 (AQP3) is closely related to diarrhea. In this study, we investigated the mechanisms of AQP3 gene expression regulation in porcine epidemic diarrhea virus (PEDV)-induced diarrhea confirmed by PCR amplification and sequencing. Evaluation of intestinal pathology showed that diarrhea caused by PEDV infection destroyed the intestinal barrier of piglets. qPCR analysis showed that AQP3 expression in the small intestine of PEDV-infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Xiao et al (51) reported that, methylation of the mC-5 site in the MUC2 promoter inhibited the binding of Yin Yang 1 (YY1) to the promoter, down regulated the expression of MUC2 and increased the susceptibility of piglets to porcine epidemic diarrhea virus (PEDV). We also have confirmed abnormal methylation at the AQP3 promoter reduce its expression in PEDV-infected piglet jejunum (52). Zhang et al (53) suggested that porcine reproductive and respiratory syndrome virus (PRRSV) vaccination in sows induces DNA methylation changes in genes and DNA methylation changes occur through intergenerational transmission.…”
Section: Discussionsupporting
confidence: 66%
“…Xiao et al (51) reported that, methylation of the mC-5 site in the MUC2 promoter inhibited the binding of Yin Yang 1 (YY1) to the promoter, down regulated the expression of MUC2 and increased the susceptibility of piglets to porcine epidemic diarrhea virus (PEDV). We also have confirmed abnormal methylation at the AQP3 promoter reduce its expression in PEDV-infected piglet jejunum (52). Zhang et al (53) suggested that porcine reproductive and respiratory syndrome virus (PRRSV) vaccination in sows induces DNA methylation changes in genes and DNA methylation changes occur through intergenerational transmission.…”
Section: Discussionsupporting
confidence: 66%
“…In addition, inhibition of AQP3 function in the colon results in diarrhea ( Ikarashi et al, 2012 ). Our previous work also showed that the expression of AQP3 was remarkably decreased in the intestinal segments of PEDV-induced piglets ( Wu et al, 2020 ), which indicates AQP3 was a potential player in modulating PEDV-induced diarrhea. However, the functions of AQP3 in cellular responses to PEDV infection and the regulatory mechanisms underlying the expression of AQP3 remain largely unknown.…”
Section: Introductionmentioning
confidence: 77%
“…In this study, M gene amplification and intestinal morphology observations showed that PEDV bands could be amplified in piglets infected with PEDV, accompanied by symptoms, such as intestinal villous atrophy, epithelial cell necrosis, and shedding. Combined with the fact that no other typical diarrheal pathogens (TGEV and PoRV) were detected in these piglets ( 28 ), PEDV was determined to be the only pathogen of infection.…”
Section: Discussionmentioning
confidence: 99%